Immediate postpartum long-acting reversible contraception in Ethiopia: A scoping review - Ritbano Ahmed Abdo; Endalew Gemechu Sendo; Erdaw Tachbele Betre; Mohammed Sultan (PLoS ONE, 2026)
Background Immediate postpartum long-acting reversible contraception (IPP-LARC) is vital for reducing unintended pregnancies and improving maternal health. Despite extensive research in Ethiopia, evidence remains fragmented. The primary objective of this scoping review was to systematically map and synthesize the available evidence on IPP-LARC in Ethiopia and identify research gaps to inform future interventions. Methods A scoping review was conducted following the JBI framework. Comprehensive searches were performed across PubMed, Cochrane Library, Hinari, Google Scholar, and grey literature sources. Studies reporting on IPP-LARC in Ethiopia were included. Data were charted and synthesized narratively. Two independent reviewers screened studies using Rayyan. Findings were presented in graphical, tabular, and narrative formats, adhering to PRISMA-ScR guidelines. Results A total of 845 records were identified through database searches and other strategies, of which 42 studies met the inclusion criteria. Among these, 42 employed quantitative designs, two were implementation-focused quality improvement studies, one used a mixed-methods approach, and one was purely qualitative. Thematic focus varied: 16 studies assessed IPP-LARC uptake, 12 examined IPP-IUCD uptake, seven evaluated intention or acceptance of LARC, one evaluated IPP-IUCD acceptance and uptake, one assessed informed choice, one examined receipt of IPPFP counseling, one explored barriers and facilitators, and one focused on knowledge and attitude. Reported uptake of immediate postpartum family planning ranged from 20.0% to 53.2%, with variation influenced by socio-demographic, service-related, psychosocial, and relational factors. Conclusion Evidence on IPP-LARC in Ethiopia highlights consistent determinants but is constrained by methodological and contextual gaps. Research remains dominated by cross-sectional, woman-centered studies, with limited attention to male engagement, community-level platforms, and qualitative insights. Addressing these gaps through rigorous, gender-inclusive, and context-sensitive intervention research is essential to strengthen shared decision-making and improve contraceptive uptake.